Uncovering Power Dynamics: Feeling Rules in European Policy‐making. (14th July 2022) - Sanchez Salgado, Rosa
Abstract: While feeling rules have been found to be highly relevant in social research and international relations, little is known about their role in European policy‐making. This article explores how emotions have been understood by Commission and Council officials and by Members of the European Parliament (MEPs) across policy areas over a long time period (1999–2014). Qualitative content analysis reveals the existence of feeling rules and that the appropriateness of emotions has been contested. Many policy‐makers, placing emotions in opposition to rationality, have claimed that policy‐making should be devoid of emotions, especially in policy areas such as public health, energy, and the environment. In contrast, in policy areas such as foreign policy and home affairs, emotions are often considered to be appropriate. This article also reflects on the role of feeling rules in constraining and enabling the policy process, uncovering subtle power dynamics. Data analysed include the European Parliament (EP) database (1999–2014) and the EUSpeech database (2007–2015).